Association between maternal socioeconomic factors, decision‐making status, and dental utilization by children with early childhood caries in sub‐urban Nigeria. (7th July 2020) - Folayan, Morenike Oluwatoyin; Alade, Micheal; Adeniyi, Abiola; El Tantawi, Maha; Finlayson, Tracy L.
Abstract: Aim: To determine the association between maternal education, income, and decision‐making status and the presence of early childhood caries (ECC) and dental‐service utilization among young children. Methods: This cross‐sectional study was based on data from a household survey of 1, 549 mother‐preschool‐aged‐child dyads conducted in Ife Central Local Government Area, Nigeria. The explanatory variables were maternal education, income, and decision‐making status (related to healthcare, large household purchases, and visits to family/relatives). Outcome variables were the presence of ECC and the child's history of dental‐service utilization. Poisson regression analyses were conducted to identify factors associated with outcomes; the models were adjusted for maternal age, child's socioeconomic status, oral hygiene status, and frequency of sugar consumption. Results: The study recruited 1, 549 mother–child dyads, of which 66 (4.3 percent) children had ECC, and 90 (5.9 percent) children had a history of dental‐service utilization. Fewer than half (42.3 percent) of the mothers earned between N18, 001(49.00) and 60, 000 (168.00) per month. Also, 896 (57.8 percent) reported not making any independent decisions, 152 (9.8 percent) made one of three decisions independently, and 313 (20.2 percent) made two or three decisions independently. In the adjusted model, children of mothers with monthly income higher than N60, 000 were more likely to have used dental services than were those whose mother's monthly income was less than or equal to N18, 000 (adjusted prevalence ratio = 2.29; 95%CI: 1.30–4.02; P = 0.004). No other maternal factor was associated with ECC. Conclusions: Although maternal socioeconomic factors and decision‐making abilities were not associated with ECC prevalence, more preschool children whose mothers had high income used dental services.